Perception of Civic Education: contributions from secondary education students. - Alfaro Valverde, Alicia (2016)
The following article presents the views of students, especially for tenth and eleven graders in secondary education about the Civic. It includes the perception they have about this subject as well as the feelings they developed around it. When students take lessons in this area, they can express strengths of this discipline regarding the integral formation of people and the necessity to reflect on communal issues relating to the environment, poverty, inequality, and strengthening democracy as a way of life. This article rescues the feelings of young people, their concerns and points of view, making it clear that this subject, at least from the "eyes of teens", is not curricular established.